Neurofascin Is a Novel Component of Rod Photoreceptor Synapses in the Outer Retina - Pourhoseini, Sahar; Goswami-Sewell, Debalina; Zuniga-Sanchez, Elizabeth (Frontiers in Neural Circuits, 2021)
Neural circuit formation is an intricate and complex process where multiple neuron types must come together to form synaptic connections at a precise location and time. How this process is orchestrated during development remains poorly understood. Cell adhesion molecules are known to play a pivotal role in assembling neural circuits. They serve as recognition molecules between corresponding synaptic partners. In this study, we identified a new player in assembling neural circuits in the outer retina, the L1-family cell adhesion molecule Neurofascin (Nfasc). Our data reveals Nfasc is expressed in the synaptic layer where photoreceptors make synaptic connections to their respective partners. A closer examination of Nfasc expression shows high levels of expression in rod bipolars but not in cone bipolars. Disruption of Nfasc using a conditional knockout allele results in selective loss of pre- and post-synaptic proteins in the rod synaptic layer but not in the cone synaptic layer. Electron microscopic analysis confirms that indeed there are abnormal synaptic structures with less dendrites of rod bipolars innervating rod terminals in loss of Nfasc animals. Consistent with these findings, we also observe a decrease in rod-driven retinal responses with disruption of Nfasc function but not in cone-driven responses. Taken together, our data suggest a new role of Nfasc in rod synapses within the mouse outer retina.